Análisis de la adaptabilidad y el rendimiento de tres variedades de pastos: ray - grass ingles (Lolium perenne), Brachiaria Brizantha (Brachiaria brizantha) y trebol blanco (Trifolium repens) en el distrito de Ayabaca Perú - Sánchez Troncos, Dalia Mariel (2013)
Improved forage varieties are used in livestock areas Ayabaca without technical knowledge adaptability and production in different ecosystems exist, especially in savanna areas, where livestock are used extensively as principal productive activity. The lack of information on adaptation and improved forage production in savanna areas motivated the study FITNESS ANALYSIS AND PERFORMANCE OF THREE VARIETIES OF PASTURES: RYEGRASS (Lolium Perennial), BRACHIARIA BRIZANTHA (Brachiaria brizantha) and CLOVER WHITE (Trifolium repens) IN THE DISTRICT OF AYABACA - PERÚ. Experimental design was used randomized block with four replications, corresponding to plots brachiaria brizantha, ray grass and White Clover English, with a duration of six months under field, for which we used 12 experimental units, with four replicates per treatment, with a size of 120 m2 experimental unit (10 * 12m), the study consisted of three phases, matching cutoff period at 90 days, in which no data were recorded only take them into account as reference second period first cut made at 50 days of making the cut equalization, the following activities were carried out data collection and foliage height for a period of seven weeks and finally the second cut after 50 days for this period also performed the above activities to the first cut. The variables evaluated were: biomass production, receptive capacity per hectare of pasture growth, pasture nutritive value and profitability of each of these will be practical analysis of variance and Duncan test was used in order to determine the best varieties or forage. The results obtained with respect to the variable biomass production was the best treatment with 3.9 Kg/m2 brizantha brachiaria, fresh matter production averaged 39 Ton/ha/cutting record, with improved profitability index 72.53 %, then ray treatment with english grass 2.95 Kg/m2 production, its production is 29.5 Ton/ha/cutting fresh state with a rate of return of 62.05% and finally the treatment of White Clover with 0.98 Kg m2, its production is 9.8 Ton/ha/cutting fresh material, likewise with a percentage yield of 1.13% . The variable capacity per hectare receptive said the treatment of brizantha can maintain 22.8 UBAS/ha/year, followed by treatment with 17.2 UBAS/ha/year ray english grass and White Clover finally with 5.7 UBAS/ha/year. In the variable pasture growth was obtained by averaging high and in the middle and two cuts of 80.63 cm high and data belonging to brachiaria brizantha, 52.50 cm and height in the ray grass English and height 21.50cm in white clover. The variables pasture nutritive value assumes very good protein levels as 16.4 % for White clover species, 13.4 % ray grass english and 8 % for the brachiaria brizantha, relative to the fiber the results are 28.3 % for brachiaria brizantha, 26.2 % and 12.2 % White Clover ray grass for english, based on cool stuff.